2020
DOI: 10.1177/0300060520959484
|View full text |Cite
|
Sign up to set email alerts
|

Rare misdiagnosed case of penicilliosis marneffei in an immunocompetent patient

Abstract: Background Penicilliosis marneffei is a rare disease caused by Talaromyces marneffei, which is endemic in Southeast Asian countries, and usually occurs in immunocompromised or immunodeficient hosts. We report an unusual misdiagnosed case of penicilliosis marneffei in an immunocompetent patient from a non-endemic area of China. Case presentation: A 59-year-old man presented to hospital with a cough and progressive hemoptysis for a 3-month period. Clinical characteristics, radiological abnormalities, and prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Moreover, two cases had hoarseness, wheezing, and hemoptysis separately when the infection involved the pharynx and airway. These features were consistent with previous reports [ 15 , 16 ]. Furthermore, TM infection involved the extra-pulmonary organs, including bone, skin, lymph nodes, and/or the central nervous system [ 17 ].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, two cases had hoarseness, wheezing, and hemoptysis separately when the infection involved the pharynx and airway. These features were consistent with previous reports [ 15 , 16 ]. Furthermore, TM infection involved the extra-pulmonary organs, including bone, skin, lymph nodes, and/or the central nervous system [ 17 ].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, two cases had hoarseness, wheezing, and hemoptysis separately when the infection involved the pharynx and airway. These features were consistent with previous reports [13,14]. Previous studies have con rmed that inhalation is the main mode of TM invasion into the body, and the lung is the most important organ for TM infection [15].…”
Section: Discussionsupporting
confidence: 92%
“… 10 It is rarely reported in immunocompetent patients. 11 However, the incidence of T. marneffei has been increasing in immunocompetent hosts. 8 , 9 , 12 A previous study reported that 22 out of 34 non-HIV patients infected with T. marneffei had no previously known diseases and no immunodeficiencies.…”
Section: Discussionmentioning
confidence: 99%